Penindakan Keimigrasian Bagi Pelaku Pemalsuan Data Dan Dokumen Untuk Mendapatkan Dokumen Perjalanan Keimigrasian - Ramadhan, Firza; Setyo Pujonggo, Seno; Wirdhiningsih, Virra (Jurnal Ilmiah Wahana Pendidikan, 2026)
Control and enforcement against data and document forgery in the context of acquiring immigration travel documents are vital elements in safeguarding national security and a nation's stability. The phenomenon of data and document forgery transcends national boundaries and creates opportunities for transnational criminal activities that undermine global stability. This research discusses the challenges and opportunities in the efforts to enforce against data and document forgery in immigration. The research highlights the importance of investing in advanced detection technology, comprehensive immigration officer training, and close international cooperation in information exchange and policy development. These actions will help enhance the effectiveness of immigration enforcement, secure national borders, and ensure the authenticity of immigration travel documents. The research also underscores the need for global immigration system updates and improvements to address forgery threats more effectively. The findings of this research provide in-depth insights into the challenges faced in enforcing against data and document forgery in immigration and serve as a foundation for further actions in maintaining national security and the integrity of immigration systems worldwide.